Penerapan Model Pembelajaran Problem Based Learning dalam Meningkatkan Hasil Belajar IPA Kelas VII SMPIT Al Khair - Masyawan Alipah; Abd. Haris; Nuraeni Nuraeni (Universitas Negeri Makassar, 2024)
This study aims to improve science learning outcomes for class VII SMPIT Al Khair in the matter of heat and its transfer. The learning model used in this research is Problem Based Learning. Data collection techniques were carried out with tests and non-tests, with instruments in the form of student activity observation sheets, teacher activity observation sheets, and final test sheets for each cycle. The procedures for implementing this research include: (1) planning, (2) implementing actions, (3) observing, and (4) reflecting in each cycle. The results of the observation of student learning activities showed an increase in each cycle. The percentage of student activity in Cycle I was 76%, Cycle II 87% and Cycle III 93%. The percentage of complete learning in Cycle I was 67%, Cycle II was 83% and Cycle III was 100%. The average learning outcomes in the first cycle is 72.22, the second cycle is 81.67 and the third cycle is 90.91. The results of the research above prove that the Problem Based Learning learning model can improve science learning outcomes for class VII SMPIT Al Khair.